Integration of Yolov8 And Instance Segmentation in The Chinese Sign Language (CSL) Recognition System - Wijaya, Mikel Ega; Handayani, Anik Nur (yocto brain, 2025)
This research aims to develop an advanced recognition system for Chinese Sign Language (CSL) by integrating YOLOv8 and instance segmentation techniques. Communication through sign language is essential for the deaf community, and although CSL has been standardized in China, recognizing complex hand movements remains a significant challenge. YOLOv8 is employed for real-time object detection, while instance segmentation is used to provide more detailed analysis of hand gestures. This integration seeks to improve hand gesture recognition under varying lighting and background conditions, which is crucial for more effective communication between the deaf community and the wider society. The study evaluates the system’s performance using common metrics such as Mean Average Precision (mAP), precision, recall, and F1-score. The findings indicate that the non-segmentation model performs better than the segmentation model in terms of precision, recall, and mAP, especially when trained with a larger dataset ratio. The non-segmentation model provides faster and more accurate detection, while the segmentation model, despite using the same amount of data, shows potential for more detailed recognition of gestures. Although the segmentation model shows improvements in the F1-score with more detailed accuracy, the non-segmentation model remains superior in overall detection speed and accuracy. This research highlights the importance of integrating YOLOv8 and instance segmentation for improving CSL recognition, with better results on the non-segmentation model for more effective communication for the deaf